Assessment of dental age estimation methods applied to Brazilian children: a systematic review and meta-analysis - Franco, Ademir (Dentomaxillofac Radiol, 2021)
OBJECTIVES: To review the scientific literature of studies on dental age estimation methods applied to Brazilian children. METHODS: A systematic literature review was designed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered in PROSPERO (CRD42020136170). Six scientific databases were used as primary search sources (PubMed, Scopus, LILACS, SciELO, Embase and Web of Science) and two databases (Open Grey and Open Thesis) were searched to partially select the “grey literature.” Only cross-sectional studies were included. The risk of bias was assessed by means of Joanna Briggs Institute Critical Appraisal Tools for Systematic Reviews. The standardized mean difference (SMD) between the estimated dental and chronological ages was meta-analysed via random effects model. RESULTS: The search resulted in 2,527 studies, from which 13 met the eligibility criteria. Out of the eligible studies, 76.92% had low risk of bias and high methodological quality. Ten studies provided proper information to be included in the meta-analysis.The methods and their SMD between estimated and chronological ages were: Willems’=0.05, Lilequist and Lundberg’s = −0.11, Nolla’s = 0.22, Mornstad’s = 0.27, Cameriere’s = −0.31, Demirjian’s = 0.74 and Haavikko’s = −0.87. CONCLUSION: Although originally trained in populations worldwide, most of the international methods for radiographical dental age estimation had optimal performance in Brazilian children.